Psychological and psychiatric impact of COVID-19 pandemic among children and adolescents.: Emotional impact of COVID-19 on children - Deolmi, Michela; Pisani, Francesco (Acta Biomedica Atenei Parmensis, 2020)
Background: COVID-19 outbreak and the unprecedent measures imposed by the government, including quarantine and social distancing, cause psychological distress in children and adolescents.Methods: we review literature about mental health effects of COVID-19 pandemic by using the keywords “COVID-19”, “coronavirus”, “pandemic”, “mental health”, “psych*”, “adolescent” and “child”.Results: early evidence show high prevalence of anxiety and depressive symptoms in children and adolescents, due to the pandemic itself, to social isolation and to parents’ stress. High grade students, females and low-income families are at higher risk to develop psychiatric symptoms. Psychological distress can be reduced by maintaining contact with peers through social networks and by accurate updates provided by the government through the mass media. Online resources such as information about mental health education and preventive measure, video-counselling, telemedicine and telepsychiatry services, can be useful to reduce the psychosocial effects of the novel coronavirus.Conclusion: there is urgent need to plan new strategies for early psychological interventions in order to reduce the impact of COVID-19 pandemic on children and adolescents mental health status.